Role of the Thalamus in Basal Forebrain Regulation of Neural Activity in the Primary Auditory Cortex. (3rd April 2020) - Azimi, H; Klaassen, A-L; Thomas, K; Harvey, M A; Rainer, G
Abstract: Many studies have implicated the basal forebrain (BF) as a potent regulator of sensory encoding even at the earliest stages of or cortical processing. The source of this regulation involves the well-documented corticopetal cholinergic projections from BF to primary cortical areas. However, the BF also projects to subcortical structures, including the thalamic reticular nucleus (TRN), which has abundant reciprocal connections with sensory thalamus. Here we present naturalistic auditory stimuli to the anesthetized rat while making simultaneous single-unit recordings from the ventral medial geniculate nucleus (MGN) and primary auditory cortex (A1) during electrical stimulation of the BF. Like primary visual cortex, we find that BF stimulation increases the trial-to-trial reliability of A1 neurons, and we relate these results to change in the response properties of MGN neurons. We discuss several lines of evidence that implicate the BF to thalamus pathway in the manifestation of BF-induced changes to cortical sensory processing and support our conclusions with supplementary TRN recordings, as well as studies in awake animals showing a strong relationship between endogenous BF activity and A1 reliability. Our findings suggest that the BF subcortical projections that modulate MGN play an important role in auditory processing.